Developing a collaborative book project on higher education pedagogy: The institutional, organizational, and community identity dimensions of student-staff partnerships - Clark, Lauren; Ribéreau-Gayon, Agathe; Sotiriou, Mina; Standen, Alex; Thorogood, Joe; Tong, Vincent C.H. (International Journal for Students as Partners, 2019)
This case study presents an ambitious student-staff partnership project at University College London (UCL) to publish a collaborative book on higher education pedagogy. Over two-and-a-half years, a total of 86 students and staff contributed to the project, which sought to provide educators with a new type of scholarly material under the unifying theme of connecting research and teaching. Multiple layers of student-staff partnership were interwoven throughout the project; this case study contextualizes these layers against three dimensions: institutional, organizational, and community identity. Central to the project was our distinctive approach to engaging with Graduate Teaching Assistants (GTAs) and their crucial role in bringing the three dimensions together. As such, the project represents a model of enhanced student-staff partnership that has the capacity to empower students and break down educational silos to form new, multi-specialty learning communities.